The Role of Mesenchymal Stem Cell in Controlling Liver Function on Liver Fibrosis - Antari, Arini Dewi; Prasetio, Ardi; Nugroho, Baskoro Adi (Journal of Science and Technology Research for Pharmacy, 2021)
ABSTRACT Background: Liver fibrosis (LF) is the end-stage of liver damage characterized by the increase concentration of SGOT and SGPT. A previous study, revealed that liver transplantation as the most effective therapy for LF has limited availability and remains a major challenge. Mesenchymal stem may control inflammation and regenerate damaged tissue leading to accelerated liver function repair. Aim: The purpose of this study was to determine the optimum doze for MSC administration to recover LF. Method: The research used variations doze of MSCs administration of 1x106 and 2x106. Liver firbosis was induced by twice a week intraperitoneal injection of carbon tetrachloride (CCl4) (Sigma-Aldrich) dissolved with olive oil in 1:1 ratio for eight weeks. The concentration of SGPT SGOT was measured at day 9 post MSC administration. One Way Anova was performed to analyze statictical data. Result: This study showed that there was a significant decrease in SGOT concentration (P < 0,05). P2 group treatment showed the lowest concentration of SGOT among the treatment (Figure B). In the same time, the administration of UC-MSCs reduce SGPT concentration insignificantly (P > 0,05). Conclusion: The transplantation of MSCs ameliorated LF by reducing SGPT and SGOT concentration